PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L.) PADA BERBAGAI DOSIS PUPUK UREA - Erawan, Dedi; Yani, Wa Ode; Bahrun, Andi (Jurnal Agroteknos, 2013)
The aim of this research was to know the effect of urea fertilizer on growth and yield of mustard plant. This research was carried out at the Experimental farm of Agriculture Faculty, Haluoleo University, from October to November 2012. This research was carried out using completely randomized block design, that consisted of 6 treatments namely: without Urea fertilizer (U0), 25 kg ha-1 equals to 1.6 g plot1 of urea fertilizer (U25), 50 kg ha-1 equals to 3,2 g plot-1 of urea fertilizer (U50), 75 kg ha-1equals to 4,8 g plot-1of urea fertilizer (U75), 100 kg ha-1 equals to 6,4 g plot-1 of urea fertilizer (U100),125 kg ha-1 equals to 8 g plot-1 of urea fertilizer (U125) . Each treatment was repeated 3 times which resulted in 18 experiment units. The experiment data were analyzed using analysis of variance method and then followed by Honest Significantly Difference Test. The result of the research showed that the application of various dosages of urea fertilizer has an effect on the growth and yield of mustard plant. The application of urea fertilizer to mustard plant effected plant height, leaf area at the age of 21 and 28 days after planting, dry weight of root, dry weight of leaves and relative growth rate. However, the application of urea fertilizer has no effect on the number of leaves, leaf area at the age of 14 days after planting, leaf fresh weight, and the root fresh weight of mustard plant. An increase in the dosages of Urea fertilizer was followed by an increase in the growth and production of mustard plant. 125 kg ha-1 urea fertilizer increased growth and production of mustard plant a lot higher compared to other of urea fertilizer with a production yield of 10 ton ha-1. Keywords: mustard plant, urea